Pengaruh Sarana Prasarana terhadap Kelancaran Proses Belajar Mengajar di MA Darul Ikhlas - Suci Nopida; Irma Suryani Siregar; Ainun Mardiah Siregar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Suci Nopida (20120034) studied the influence of infrastructure on the smoothness of the teaching and learning process at MA Darul Ikhlas, Dalan Lidang, Panyabungan District. This research aims to answer three problem formulations: 1) Is there an influence of infrastructure on the smoothness of teaching and learning? 2) What is the condition of the infrastructure at MA Darul Ikhlas? 3) What are the factors that influence the smoothness of the teaching and learning process?. The research method used was a mixed method with a stratified proportional random sampling technique, involving 252 students. The use of a Likert scale-based questionnaire produced 23 valid statements for infrastructure and 22 for the smoothness of the teaching and learning process. The research results show that the infrastructure at MA Darul Ikhlas is not yet complete, with deficiencies such as laboratory equipment and projectors. Three factors that influence the teaching and learning process are infrastructure, teacher professionalism, and student interest in learning. The influence of infrastructure on the smoothness of the teaching and learning process is 44.5%. Hypothesis testing shows significance, so it can be concluded that there is a significant influence between infrastructure and the smoothness of the teaching and learning process.